2019
DOI: 10.1155/2019/5801570
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Concentration of Salivary Tyrosine and Antioxidants in Patients with Oral Lichen Planus

Abstract: The diagnosis of oral lichen planus (OLP) is based on clinical examination and histopathological criteria. Noninvasive diagnostics of saliva may be considered as a confirmation of OLP diagnosis and a potential alternative to an invasive method. The objective of the present study was to evaluate the relationship between the level of tyrosine (Tyr) as well as antioxidants like uric acid (UA) and glutathione peroxidase (GPx) activity in the saliva of patients with OLP in comparison with the control group (healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Forty percent of the total salivary antioxidant barrier is provided by bloodborne uric acid (UA) [ 5 ]. Failure of these antioxidant systems may result in the development of oral cavity diseases, including periodontitis [ 9 , 10 ], precancerous lesions [ 11 ] and cancers [ 12 ]. Previous studies showed the alteration in the salivary antioxidants barrier and the contribution of OS in the development and progression of salivary gland dysfunction in the course of other autoimmune diseases: psoriasis vulgaris, systemic sclerosis, rheumatoid arthritis, diabetes type 1, multiple sclerosis, Sjögren’s syndrome and systemic lupus erythematosus [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forty percent of the total salivary antioxidant barrier is provided by bloodborne uric acid (UA) [ 5 ]. Failure of these antioxidant systems may result in the development of oral cavity diseases, including periodontitis [ 9 , 10 ], precancerous lesions [ 11 ] and cancers [ 12 ]. Previous studies showed the alteration in the salivary antioxidants barrier and the contribution of OS in the development and progression of salivary gland dysfunction in the course of other autoimmune diseases: psoriasis vulgaris, systemic sclerosis, rheumatoid arthritis, diabetes type 1, multiple sclerosis, Sjögren’s syndrome and systemic lupus erythematosus [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Glutathione Peroxidase (GPx) . In saliva, three studies all reported significantly lower GPx in OLP cases, while there was no significant association of GPx with OLP across the meta-analyses [ 29 , 35 , 42 ]. In addition, GPx in serum [ 29 ] (30 patients), thiol in serum [ 15 ] (22 patients), and GSH in saliva [ 32 ] (62 patients) were determined in the single study, and decreased levels were found.…”
Section: Resultsmentioning
confidence: 99%
“…UA in plasma/serum was investigated in three studies and found to be markedly decreased in OLP compared to controls (effect size -1.19, 95% CI -1.83, -0.54), with statistically significant heterogeneity ( P = 0.008, I 2 = 80%) [ 29 , 43 , 44 ]. Four studies reported lower salivary UA in OLP cases [ 29 , 42 , 44 , 45 ], while one single study did not report any statistically significant difference between OLP and controls [ 35 ]. The meta-analysis for UA assessed in saliva was -2.65 (95% CI -4.20, -1.09), with statistically significant heterogeneity ( P < 0.00001, I 2 = 97%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations